2019
DOI: 10.1098/rsos.191086
|View full text |Cite
|
Sign up to set email alerts
|

Formation of neural networks with structural and functional features consistent with small-world network topology on surface-grafted polymer particles

Abstract: In vitro electrophysiological investigation of neural activity at a network level holds tremendous potential for elucidating underlying features of brain function (and dysfunction). In standard neural network modelling systems, however, the fundamental three-dimensional (3D) character of the brain is a largely disregarded feature. This widely applied neuroscientific strategy affects several aspects of the structure–function relationships of the resulting networks, altering network connectivity and topology, ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…4-7 and Supplementary Figs. [16][17][18][19][20][21][22][23][24][25][26], the culture medium was fully replaced after one day with a fresh medium that contained 5 μL of AAV-EF1α-hChR2(H134R)-eGFP virus (1.25 × 10 12 GC⋅mL −1 , KIST Virus Facility). After two more days, half of the medium was replaced with a fresh medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4-7 and Supplementary Figs. [16][17][18][19][20][21][22][23][24][25][26], the culture medium was fully replaced after one day with a fresh medium that contained 5 μL of AAV-EF1α-hChR2(H134R)-eGFP virus (1.25 × 10 12 GC⋅mL −1 , KIST Virus Facility). After two more days, half of the medium was replaced with a fresh medium.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the emerging advancements of engineered 3D neural circuit models, technologies for both precisely monitoring and modulating neural activities within the neural circuit models in vitro have not been developed yet. Calcium imaging or planar extracellular electrophysiology with a 2D microelectrode array (MEA), which are the tools that are commonly used in 2D cultures of neurons in vitro, remain the mainstream methodologies for monitoring neural activities in 3D in vitro models [14][15][16][17][18][19][20] . A significant disadvantage of these measurement techniques is the difficulty of analyzing the neuronal connections and the dynamics of the neural network in a 3D microenvironment.…”
mentioning
confidence: 99%
“…In addition, there is tangible evidence that neural networks inherently have the characteristics of small-world networks: almost every neuron is linked with each other through only a few connections 31 , 32 . So, adding countable functional connections can revolutionize inhomogeneous neuronal networks 33 .…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest in the last decade to develop in vitro 3-D neural cell culture models [11][12][13] and correspondingly increasing reports of measurement of electrophysiological activity of dissociated 3-D neural cultures are being published using different culture configurations and recording techniques [14][15][16][17][18][19][20][21]. Previously, performing patch clamp recordings, our group showed that dissociated cortical neurons cultured in the 3-D neural culture model that we developed within Matrigel™ are electrophysiologically active [14].…”
Section: Introductionmentioning
confidence: 99%